O03.6 Using Molecular Typing to Investigate N. Gonorrhoeae Strain Turnover: A Comparative Study of GISP Isolates Collected from Baltimore and San Francisco. (13th July 2013) - Espinosa, K; Gerrity, J; Pandori, M; Marsiglia, V; Hardick, J; Barnes, M; Hess, D; Gaydos, C
Abstract : Background: One internationally accepted method for the molecular epidemiologic typing of Neisseria gonorrhoeae is Neisseria gonorrhoeae Multi Antigen Sequence Typing (NG-MAST). NG-MAST utilises DNA sequencing of two variable regions of the N. gonorrhoeae genome to classify gonococcal isolates into strain types. Method: We assessed the genetic diversity of N. gonorrhoeae isolates in Baltimore (N = 277) spanning the years 2009–2011 compared to San Francisco (N = 539) from 2005–2011, using NG-MAST. All isolates in this project were obtained from the CDC Gonococcal Isolate Surveillance Project (GISP). San Francisco strains were mostly from MSM, while the Baltimore isolates were mostly from a heterosexual population. Results: NG-MAST results from isolates across that time period revealed a surprising degree of sequence type turnover within the Baltimore area. When compared to the data from San Francisco, the N. gonorrhoeae genetic diversity trends revealed minimal overlap in sequence families between the two metropolitan areas; SF8238, SF210, and SF 2992 were present in both populations. However, a pair-wise comparison of other strain families revealed two relatively distinct populations; the most prevalent strain families in San Francisco were SF437, SF23, SF3935, and SF1407, while those in Baltimore were SF8234, SF8240, SF865, and SF8262. Conclusion: These data may imply that the traditional understanding of a gonococcal transmission pattern from west to east cannot accurately depict the strain flow of N. gonorrhoeae isolates within these populations. Our data revealed a large amount of strain turnover in both metropolitan areas by year. This raises questions about the entry and transmission of N. gonorrhoeae within the U.S., and the implications of this turnover in regards to the evolution of this organism.